2015
DOI: 10.1016/j.freeradbiomed.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase formation of PAF receptor ligands induces PAF receptor-dependent kidney injury during ethanol consumption

Abstract: Cytochrome P450 2E1 (CYP2E1) induction and oxidative metabolism of ethanol in hepatocytes inflames and damages liver. Chronic ethanol ingestion also induces kidney dysfunction, which associates with mortality of alcoholic hepatitis. Whether kidney is directly affected by ethanol or is secondary to liver damage is not established. We found CYP2E1 was induced in kidney tubules of mice chronically ingesting a modified Lieber-deCarli liquid ethanol diet. Phospholipids of kidney tubules were oxidized and fragmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…The anti-inflammatory action of TAU, evidenced in the current study, confirms previous findings of [54], who demonstrated the effective role of TAU as an antiinflammatory supplement when given to alleviate the inflammation induced in the kidney by chronic ethanol ingestion.…”
Section: Discussionsupporting
confidence: 91%
“…The anti-inflammatory action of TAU, evidenced in the current study, confirms previous findings of [54], who demonstrated the effective role of TAU as an antiinflammatory supplement when given to alleviate the inflammation induced in the kidney by chronic ethanol ingestion.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, chronic ethanol administration in rats and mice results in increased levels of oxidized GPCs and PAF in plasma (Liu et al, 2013;Yang et al, 2010). Moreover, PAF-Redeficient mice are protected from chronic ethanol-mediated kidney damage (Latchoumycandane et al, 2015). In these chronic ethanol models, nonenzymatic oxidized GPC PAF agonists appear to play important roles, whereas the present acute ethanol and thermal injury model involves enzymatic PAF agonists.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, Grossmann et al observed a state of low‐grade inflammation in insulin‐resistant patients . Previous research showed that ethanol‐fed rats have significantly decreased renal catalase, SOD and glutathione levels and increased MDA, MPO and inflammatory mediator levels …”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcoholism induces expression of the ethanol metabolising enzyme cytochrome P450 2E1 (CYP2E1), particularly in the kidneys . This enzyme modifies phospholipids in cell membranes, which activates neutrophil granulocytes and aggravates oxidative stress …”
Section: Introductionmentioning
confidence: 99%